EXPLORATORY FACTORS ANALYSIS OF EFFECTIVE TEAMWORK OF THE ACCOUNTANTS IN INDUSTRIAL BUSINESS IN EASTERN REGION - Phumsiri, Nattapol (RMUTT Global Business and Economics Review, 2019)
Since 2014, Thailand has increased the number of business registrations. At the same time, employee’s turnover rate has also increased. This leads to a shortage of accountants and financial positions which are highly required for the business. The objectives of this research were to study the model of the accountant’s teamwork and analyze factors of effective accountant’s teamwork in industrial business in Eastern region. The sample was sampling from accountants in industrial business in Eastern region which proportional distribution, accounting for 1,302 persons. The data was collected by interview. The statistics used for data analysis were frequency, percentage, mean, standard deviation, and exploratory factor analysis of effective teamwork of accountants in industrial business in eastern region. Research results can be summarized as follows; 1) For overall, the importance of the effective teamwork of the accounts was in high level. When considered by aspect, the importance of human relations aspect, leadership aspect, communication aspect, and team member aspect were in high level, respectively 2) the results of exploratory factor analysis revealed that the effective accountant teamwork was comprising of 4 components including Leadership aspect, which emphasized on leaders must be fair and non-bias, Human relations aspect, which emphasized on teamwork must consist of good listeners, Team member aspect, which emphasized on team work must have the responsibility, and Communication aspect, which emphasized on the team has opportunities to advice the organization, and 3) Analysis of correlation coefficients found the significant relationship between the variables of the effective accountant’s teamwork in industrial business in Eastern region with statistical significance at 0.001, accounting for 528 pairs. The most relevant relationship was listening to everyone’s opinions and giving the opportunity to express opinions, with the correlation coefficients at 0.655.